Multimodal optical imaging and genetic features of AB variant GM2 gangliosidosis: a case report - Chen, Qin; Lu, Fang (Frontiers in Pediatrics, 2023)
Background：AB variant GM2 gangliosidosis is an extremely rare autosomal recessive lysosomal storage diseases. Macular cherry-red spots are the most commonly described ocular sign in this disease. We first report an infant case of AB variant GM2 gangliosidosis with multimodal optical imaging and genetic testing results. Case description：A seven-month-old Chinese girl presented to the hospital with nystagmus for 2 months. The family history was negative, and the parents were not known to be consanguineous. Fundus photography showed a cherry-red spot with a ring of whitish infiltrate surrounding both macula. Fluorescein angiography showed normal retinal circulation and vessels. Optical coherence tomography (OCT) revealed thickening and increased reflectivity of the inner retinal layers with a shadowing effect on outer structures. The patient had no obvious neurological symptoms, and the MRI of the head was normal. The exome genome sequencing results showed that there was homozygous deletion (chr5: 150639196-150639548) of exon 2 in the GM2A gene. Finally, the patient was diagnosed with AB variant GM2 gangliosidosis. Conclusions：AB variant GM2 gangliosidosis is a rare disease affecting multiple nervous systems. Before typical neurological symptoms appear, the clinical features of fundus photography and OCT help us diagnose GM2 gangliosidosis